Do plant sterol concentrations correlate with coronary artery disease in type 1 diabetes? A report from the Pittsburgh Epidemiology of Diabetes Complications Study - SHAY, Christina Marie (2009)
BACKGROUND: It has been suggested that plant sterol absorption is increased in type 1 diabetes mellitus (T1DM) and that this may relate to the increased cardiovascular risk seen in T1DM. The cardiovascular benefit of lowering low-density lipoprotein–cholesterol with statin medication has also been shown to be influenced by plant sterol absorption. METHODS: The relationship between sterol concentrations, coronary artery disease (CAD), and the use of statin medications in T1DM was compared between participants with CAD (Minnesota codes 1.1, 1.2, 1.3, 4.1–4.3, 5.1–5.3, and 7.1; n = 82), from the Pittsburgh Epidemiology of Diabetes Complications (EDC) study, and those without (n = 213). Serum sterol concentrations reflecting cholesterol absorption (β-sitosterol and campesterol) and synthesis (desmosterol and lathosterol) were assayed and analyzed by gas chromatography and were expressed as a ratio of total cholesterol (×10(3)). RESULTS: No differences were observed in markers of cholesterol absorption between individuals with and without CAD. In patients with CAD, significantly lower levels were observed for both sterol markers reflecting cholesterol synthesis compared with individuals without CAD [desmosterol: 0.34 vs 0.42, respectively (P = 0.003); lathosterol 0.47 vs 0.54, respectively (P = 0.019)]. Further stratification by statin medication use revealed significantly lower levels of synthesis-reflecting sterols in individuals taking statin medication, particularly those with CAD. CONCLUSIONS: Although previous reports suggest that higher levels of cholesterol absorption in T1DM potentially increase cardiovascular risk in this population, the present data suggest no differences in cholesterol absorption between T1DM individuals with and without CAD.